Impact of obesity on airway remodeling in asthma: pathophysiological insights and clinical implications - Listyoko, Aditya Sri; Okazaki, Ryota; Harada, Tomoya; Inui, Genki; Yamasaki, Akira (Frontiers in Allergy, 2024)
The prevalence of obesity among asthma patients has surged in recent years, posing a significant risk factor for uncontrolled asthma. Beyond its impact on asthma severity and patients' quality of life, obesity is associated with reduced lung function, increased asthma exacerbations, hospitalizations, heightened airway hyperresponsiveness, and elevated asthma-related mortality. Obesity may lead to metabolic dysfunction and immune dysregulation, fostering chronic inflammation characterized by increased pro-inflammatory mediators and adipocytokines, elevated reactive oxygen species, and reduced antioxidant activity. This chronic inflammation holds the potential to induce airway remodeling in individuals with asthma and obesity. Airway remodeling encompasses structural and pathological changes, involving alterations in the airway's epithelial and subepithelial layers, hyperplasia and hypertrophy of airway smooth muscle, and changes in airway vascularity. In individuals with asthma and obesity, airway remodeling may underlie heightened airway hyperresponsiveness and increased asthma severity, ultimately contributing to the development of persistent airflow limitation, declining lung function, and a potential increase in asthma-related mortality. Despite efforts to address the impact of obesity on asthma outcomes, the intricate mechanisms linking obesity to asthma pathophysiology, particularly concerning airway remodeling, remain incompletely understood. This comprehensive review discusses current research investigating the influence of obesity on airway remodeling, to enhance our understanding of obesity's role in the context of asthma airway remodeling.